1995
DOI: 10.1111/j.1442-2042.1995.tb00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Microvessel Count in Low Stage Renal Cell Carcinoma

Abstract: Assessment of tumor microvasculature is therefore probably one of the most important prognostic predictors in renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 16 publications
2
51
0
1
Order By: Relevance
“…In contrast, other reports have shown that MVD is a better predictor for the metachronous metastasis of RCC than many other factors. 54 In support of these reports, we have shown that MVD is significantly higher in the primary tumor of patients with metastatic CRCC compared with patients with nonmetastatic CRCC. Furthermore, MVD is higher in the tumor metachronously metastasized than in the primary tumor of patients with metastatic CRCC.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, other reports have shown that MVD is a better predictor for the metachronous metastasis of RCC than many other factors. 54 In support of these reports, we have shown that MVD is significantly higher in the primary tumor of patients with metastatic CRCC compared with patients with nonmetastatic CRCC. Furthermore, MVD is higher in the tumor metachronously metastasized than in the primary tumor of patients with metastatic CRCC.…”
Section: Discussionsupporting
confidence: 78%
“…As summarized in Table 1, higher MVD has been reported in many studies to be a favorable prognostic factor (eg, a higher blood vessel density in CCRCC is correlated with a better prognosis or longer patient survival). 4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 55%
“…Even though all the patients at the time There are numerous studies in the literature showing that MVD correlates with aggressive tumor behavior, as measured by decreased patient survival, increase incidence of metastasis, and higher stage at presentation. Weidner and colleagues first showed this relationship in patients with breast carcinoma [3], with MVD further shown to be a predictor of aggressive tumor behavior in patients with head-and-neck squamous cell carcinoma, non-small-cell lung carcinoma, cholangiocarcinoma, transitional cell carcinoma of the bladder, renal cell carcinoma, prostate carcinoma, ovarian carcinoma, and cervical squamous cell carcinoma [6][7][8][9][10][11][12][13][14]. MVD has also been previously explored in cutaneous malignant melanoma with some studies showing them to have significantly higher MVD counts then benign nevi [15,16].…”
Section: Discussionmentioning
confidence: 99%